NANOEMULSION-BASED BIOPESTICIDE FROM LEMONGRASS, GARLIC, AND CIGARETTE BUTTS FOR CONTROLLING Fusarium WILT IN PATCHOULI (Pogostemon Cablin) - Isdaryanti Isdaryanti; Yusrianto Nasir; Sri Sukmawati; Alexander Kurniawan Sariyanto Putera (BIOLINK (Jurnal Biologi Lingkungan Industri Kesehatan), 2026)
Diseases of patchouli (Pogostemon cablin) caused by fungal pathogens are a major constraint to crop productivity and oil quality, highlighting the need for effective and environmentally friendly control strategies. This study aimed to evaluate the physicochemical characteristics, antifungal activity, and in vivo effectiveness of fermented biopesticide formulations derived from garlic (Allium sativum), lemongrass (Cymbopogon citratus), and cigarette butts. The research consisted of formulation and fermentation using EM4, analysis of physicochemical properties, in vitro antifungal assays against two fungal pathogens at different concentrations, and in vivo evaluation of disease incidence and plant growth. The results showed that fermentation significantly reduced pH, indicating active microbial metabolism. In vitro tests demonstrated that both formulation type and concentration significantly affected mycelial growth inhibition, with formulations F1 and F2 exhibiting the highest antifungal activity and near-complete inhibition at higher concentrations. In vivo application confirmed these results, as F1 and F2 significantly reduced disease incidence and improved plant growth compared to the control. In conclusion, fermented biopesticide formulations, particularly F1 and F2, have strong potential as effective and environmentally friendly alternatives for managing patchouli diseases and supporting sustainable agriculture.